Impact of pharmacist‐involved collaborative care on the clinical, humanistic and cost outcomes of high‐risk patients with type 2 diabetes (IMPACT): a randomized controlled trial. (27th April 2017) - Siaw, M. Y. L.; Ko, Y.; Malone, D. C.; Tsou, K. Y. K.; Lew, Y.‐J.; Foo, D.; Tan, E.; Chan, S. C.; Chia, A.; Sinaram, S. S.; Goh, K. C.; Lee, J. Y.‐C.
Summary: What is known and objective: With the increasing prevalence of diabetes, the physician‐centred model is challenged to deliver holistic care in Asia. Diabetes may be managed effectively within a multidisciplinary collaborative care model; however, evidence on its effectiveness in Asian patients is lacking. Therefore, the primary objective was to evaluate the clinical outcomes of multidisciplinary collaborative care vs physician‐centred care in diabetes. The secondary objectives were to evaluate humanistic and economic outcomes among the two types of care. Methods: This 6‐month prospective, open‐label, parallel‐arm, randomized, controlled study was conducted at four outpatient healthcare institutions. High‐risk patients aged ≥21 years with uncontrolled type 2 diabetes, polypharmacy and comorbidities were included. Patients with type 1 diabetes or those who were unable to communicate independently were excluded. The control arm received usual care with referrals to nurses and dietitians as needed. The intervention arm (multidisciplinary collaborative care) was followed up with pharmacists regularly, in addition to receiving the usual care. The primary outcomes included HbA1c, systolic blood pressure, low‐density lipoprotein and triglycerides. The secondary outcomes included scores from the Problem Areas in Diabetes (PAID) and the Diabetes Treatment Satisfaction Questionnaires (DTSQ), and diabetes‐related health service utilization rates and costs. Results and discussion: Of 411 eligible patients, 214 and 197 patients were randomized into the intervention and control arms, respectively. At 6 months, 141 patients in the intervention arm (65.9%) and 189 patients in the control arm (95.9%) completed the study. Mean HbA1c reduced from 8.6%±1.5% at baseline to 8.1%±1.3% at 6 months in the intervention arm ( P =.04), with up to mean HbA1c improvement of 0.8% in patients with greater levels of uncontrolled glycemia. Whereas the mean HbA1c in the control arm remained unchanged (8.5%±1.4%) throughout the 6‐month period. Improvements in PAID and DTSQ scores, reduction in physician workload and an average cost savings of US$91.01 per patient were observed in the intervention arm over 6 months. What is new and conclusions: The positive clinical, humanistic and economic outcomes highlighted the value of multidisciplinary collaborative care for Asian diabetic patients, thereby supporting the effectiveness of this approach in managing chronic diseases.